Mental Health‐Related Emergency Department Visits Among Children During The Early COVID‐19 Pandemic. Issue 1 (23rd February 2022) - Edgcomb, Juliet Beni; Benson, Nicole M.; Tseng, Chi‐hong; Thiruvalluru, Rohith; Pathak, Jyotishman; Bussing, Regina; Harle, Christopher A.; Zima, Bonnie T.
Abstract : Objective: To measure univariate and covariate‐adjusted trends in children's mental health‐related emergency department (MH‐ED) use across geographically diverse areas of the U.S. during the first wave of the Coronavirus‐2019 (COVID‐19) pandemic. Method: This is a retrospective, cross‐sectional cohort study using electronic health records from four academic health systems, comparing percent volume change and adjusted risk of child MH‐ED visits among children aged 3–17 years, matched on 36‐week (3/18/19–11/25/19 vs. 3/16/20–11/22/20) and 12‐week seasonal time intervals. Adjusted incidence rate ratios (IRR) were calculated using multivariate Poisson regression. Results: Visits declined during spring‐fall 2020 ( n  = 3892 vs. n  = 5228, −25.5%) and during spring ( n  = 1051 vs. n  = 1839, −42.8%), summer ( n  = 1430 vs. n  = 1469, −2.6%), and fall ( n  = 1411 vs. n  = 1920, −26.5%), compared with 2019. There were greater declines among males (28.2% vs. females −22.9%), children 6–12‐year (−28.6% vs. −25.9% for 3–5 years and −22.9% for 13–17 years), and Black children (−34.8% vs. −17.7% to −24.9%). Visits also declined for developmental disorders (−17.0%) and childhood‐onset disorders (e.g., attention deficit and hyperactivity disorders; −18.0%). During summer‐fall 2020, suicide‐related visits rose (summer +29.8%, fall +20.4%), but were not significantly elevated from 2019 when controlling for demographic shifts. In contrast, MH‐ED use during spring‐fall 2020 was significantly reduced for intellectual disabilities (IRR 0.62 [95% CI 0.47–0.86]), developmental disorders (IRR 0.71 [0.54–0.92]), and childhood‐onset disorders (IRR 0.74 [0.56–0.97]). Conclusions: The early pandemic brought overall declines in child MH‐ED use alongside co‐occurring demographic and diagnostic shifts. Children vulnerable to missed detection during instructional disruptions experienced disproportionate declines, suggesting need for future longitudinal research in this population. HIGHLIGHTS: Children's mental health (MH)‐related Emergency department (ED) use declined during spring‐fall 2020 (−25.5%) compared with 2019, with the greatest reduction during spring (−42.8%) and fall (−26.5%), and lesser reduction during summer (−2.6%) During summer‐fall 2020, suicide‐related visits rose (summer +29.8%, fall +20.4%), but were not significantly elevated from 2019 when controlling for demographic shifts in use Children's MH‐related ED use during spring‐fall 2020 was significantly reduced for intellectual disabilities (incidence rate ratios [IRR] 0.62 [95% CI 0.47–0.86]), developmental disorders (IRR 0.71 [0.54–0.92]), and childhood‐onset disorders (IRR 0.74 [0.56–0.97])